2000
DOI: 10.1002/chin.200029181
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of 10,11‐Didehydro Cinchona Alkaloids and Key Derivatives.

Abstract: A series of 10,11-didehydro Cinchona alkaloids containing an ethynyl group at C(3) were prepared efficiently in two steps from the naturally occurring Cinchona alkaloids (Scheme 1). 10,11-Didehydroquinine (4c) and 10,11-didehydroquinidine (4a) belong to a significantly new class of semi-natural Cinchona alkaloids. They are more polar and basic than the natural compounds and serve as versatile building blocks for further functionalization; they were transformed into the corresponding 11-halo and 11-pseudohalo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The vinyl group in the alkaloids can also be converted to a terminal alkyne by bromine addition followed by two HBr elimination reactions [ 139 , 140 ]. The alkynes QN-11 and QD-11 (didehydroalkaloids) were then directly coupled in a Sonogashira-type oxidation reaction.…”
Section: -Vinyl Groupmentioning
confidence: 99%
“…The vinyl group in the alkaloids can also be converted to a terminal alkyne by bromine addition followed by two HBr elimination reactions [ 139 , 140 ]. The alkynes QN-11 and QD-11 (didehydroalkaloids) were then directly coupled in a Sonogashira-type oxidation reaction.…”
Section: -Vinyl Groupmentioning
confidence: 99%
“…As compared with the reported strategy, 22 the described procedure offers the advantages of robustness, scalability, operational simplicity, use of as-received solvents, and chromatography-free work-up. We are confident that with the now ready access of didehydro Cinchona alkaloids, these versatile scaffolds will see frequent future use in the fields of asymmetric synthesis and chiral recognition.…”
Section: Resultsmentioning
confidence: 93%
“…Considerable efforts to establish a double dehydrobromination procedure were also described by Hoffmann's group, who screened different types of bases in a range of solvents and at various temperatures. 22 However, the yields of the chromatographically isolated didehydro Cinchona alkaloids did generally not exceed 50%, with increasing temperature and extended reaction times further compromising product recovery because of decomposition. From these observations, we concluded that successful double dehydrobromination demands a set of carefully matched reaction condi- Scheme 2 tions, including relatively mild bases and low temperatures.…”
Section: Results and Discussion Synthetic Route Is Shown In Schemementioning
confidence: 98%
See 2 more Smart Citations